Drug evaluation review: dupilumab in atopic dermatitis. (October 2015) - Hamilton, Jennifer D; Ungar, Benjamin; Guttman-Yassky, Emma
Atopic dermatitis (AD) is characterized by type 2 helper T (Th2) cell-driven inflammation. Dupilumab is a fully human monoclonal antibody directed against the IL-4 receptor α subunit that blocks the signaling of IL-4 and IL-13, both key cytokines in Th2-mediated pathways. In Phase I and II studies of adults with moderate-to-severe AD, dupilumab administered as monotherapy or with topical corticosteroids resulted in rapid, significant improvements in clinical efficacy, patient-reported outcomes, and Th2-related serum and tissue biomarkers, and shifted the RNA expression profile of lesional skin to a more nonlesional signature. In all clinical studies to date, dupilumab has shown a favorable safety profile with no dose-limiting toxicity. The robust effects of dupilumab on skin inflammation and pruritus confirm the pathogenic role of IL-4 and IL-13 signaling in adult AD, and further support the application of Th2 cytokine antagonists in the treatment of this disease.